SN 2020zbf: A fast-rising hydrogen-poor superluminous supernova with strong carbon lines - Gkini, A. (EDP Sciences, 2025)
SN 2020zbf is a hydrogen-poor superluminous supernova (SLSN) at z = 0.1947 that shows conspicuous C II features at early times, in contrast to the majority of H-poor SLSNe. Its peak magnitude is Mg = −21.2 mag and its rise time (≲26.4 days from first light) places SN 2020zbf among the fastest rising type I SLSNe. We used spectra taken from ultraviolet (UV) to near-infrared wavelengths to identify spectral features. We paid particular attention to the C II lines as they present distinctive characteristics when compared to other events. We also analyzed UV and optical photometric data and modeled the light curves considering three different powering mechanisms: radioactive decay of 56Ni, magnetar spin-down, and circumstellar medium (CSM) interaction. The spectra of SN 2020zbf match the model spectra of a C-rich low-mass magnetar-powered supernova model well. This is consistent with our light curve modeling, which supports a magnetar-powered event with an ejecta mass Mej = 1.5 M⊙. However, we cannot discard the CSM-interaction model as it may also reproduce the observed features. The interaction with H-poor, carbon-oxygen CSM near peak light could explain the presence of C II emission lines. A short plateau in the light curve around 35–45 days after peak, in combination with the presence of an emission line at 6580 Å, can also be interpreted as being due to a late interaction with an extended H-rich CSM. Both the magnetar and CSM-interaction models of SN 2020zbf indicate that the progenitor mass at the time of explosion is between 2 and 5 M⊙. Modeling the spectral energy distribution of the host galaxy reveals a host mass of 108.7 M⊙, a star formation rate of 0.24−0.12+0.41 M⊙ yr−1, and a metallicity of ∼0.4 Z⊙.